Applied Data Science for Exploring Critical Factors Affecting Systemic Risk of Commercial Banks in Vietnam - Nga, Lu Phi; Tam, Phan Thanh (Bright Publisher, 2025)
The banking system is essential in developing the Vietnamese economy, serving as a capital supply channel for the economy's production, business, and investment activities. In 2024, the banking industry faces many challenges, including global macroeconomic fluctuations, the Russia-Ukraina war, and policy changes. Therefore, the study aims to quantify the impact of these factors on systemic risk using a Structural Equation Modeling (SEM) approach. Furthermore, it seeks to provide empirical evidence and actionable policy recommendations to help mitigate systemic risks, enhance financial stability, and support socio-economic recovery and development. The methodology of this study applied a structural equation model consisting of five factors: (1) Macroeconomic environment, (2) internal factors of commercial banks, (3) legal framework and supervisory authorities, (4) globalization and financial integration, and (5) technology and financial innovation. Data were collected from 450 managers working in the banking sector and processed using Amos software. The study's novelty showed that five critical factors positively impact the systemic risk of commercial banks in Vietnam. In addition, the originality of this research includes introducing technology and financial innovation into the model, a new factor of the banking industry in the digital transformation period of banking. Moreover, the results highlight that robust and timely policy interventions are essential for mitigating systemic vulnerabilities and promoting financial stability. Finally, the practical implications of the article proposed policy recommendations to help managers and policymakers minimize systemic risks due to influences from external-internal factors contributing to socio-economic recovery and development. Finally, managers and policymakers should strengthen regulatory oversight, promote digital risk management, enhance governance practices, and ensure macroeconomic stability to mitigate systemic banking risk.